Marketing Digital no Varejo Online Durante a Pandemia: Uma Análise Netnográfica - Carvalho, Marcelo; da Silva, Cesar Augusto (Retail Management Review, 2025)
Objective: This study aims to analyze the digital marketing strategies adopted by major Brazilian retailers during the COVID-19 pandemic, with a focus on the interactions generated on social media. Methodology: A netnographic study was conducted using the social media platform Facebook. Data were collected from the official marketplace pages of Casas Bahia and Magazine Luiza, covering a six-month period from March to September 2020. Originality: This context allowed for the examination of a period marked by increased use of digital technologies and changes in the consumer experience, offering opportunities for strategic shifts in the management of online retail. Main results: The netnographic model proved effective in understanding consumers’ digital behavior. Posts featuring promotional elements, videos, calls to action, and socially relevant themes tended to generate a higher number of shares, a metric regarded as the most valuable in terms of organic reach. Theoretical Contributions: This study contributes by empirically demonstrating how different content strategies affect engagement on social media. The findings reinforce the importance of qualitative metrics, such as shares, as indicators of perceived value and potential for virality.